AAN position statement: Ethical issues in clinical research in neurology. (14th April 2020) - Tolchin, Benjamin; Conwit, Robin; Epstein, Leon G.; Russell, James A.
Abstract : This update to the American Academy of Neurology's 1998 position statement endeavors to provide guidance for the consistent ethical conduct and review of neurologic research involving human participants. It does so by outlining a widely used ethical framework of 7 principles derived from the foundational documents of modern bioethics, including the Nuremberg Code, the World Medical Association's Declaration of Helsinki, the Belmont Report, and the US Department of Health and Human Service's Common Rule. The position statement then applies this principle-based framework to analyze and produce recommendations for the management of common and important ethical issues encountered in neurologic clinical research. These include institutional review board oversight, equitable research participant inclusion, cognitive impairment in research participants, international studies, the replication crisis, and genetic testing and modification.